Older adults’ preferences for technological nutrition education - Perversi, Maria E. (Kansas State University, 2007)
The use of computer-based and personal assistive technology is projected to increase as the boomer generation continues to age. Technology is infiltrating and improving the lives of older adults, including their education. This study determined older adults’ preferences toward the use of technology to learn about nutrition and health. The sample included 132 volunteer subjects, mostly female, white non-Hispanic, ranging in age from 65−92 years, recruited from local organizations, senior centers, churches, and senior apartments. All participants completed a newly developed, 32-item pilot tested questionnaire that included demographic and self-rated health characteristics, current use of technology, factors that motivate and/or influence attitudes and interest toward use of technology, and preferred formats and topics of interest for nutrition and health education information. The results indicated that, overall, these older adults self-rated their health as either excellent or good, and that those who were younger and among the higher income brackets and education levels were more likely to use computers than those who were older, with less income, and education levels. Findings also indicated that older adults were interested and willing to learn about technology, had positive attitudes toward it and showed a high demand for user-friendly programs and training. Finally, results show that although newsletters, magazines and television were mostly preferred by older adults, computers were also considered very helpful and were used to learn about nutrition and health information.
Keywords: older adults; technology; preferences; nutrition education; educational formats; Health Sciences, Nutrition (0570)